Inhibition of Dipeptidyl Peptidase-4 by Flavonoids: Structure–Activity Relationship, Kinetics and Interaction Mechanism - Pan, Junkun; Zhang, Qiang; Zhang, Chunling; Yang, Wenbo; Liu, Hui; Lv, Zhenzhen; Liu, Jiechao; Jiao, Zhonggao (Frontiers in Nutrition, 2022)
With the aim to establish a structure-inhibitory activity relationship of flavonoids against dipeptidyl peptidase-4 (DPP-4) and elucidate the interaction mechanisms between them, a pannel of 70 structurally diverse flavonoids was used to evaluate their inhibitory activities against DPP-4, among which myricetin, hyperoside, narcissoside, cyanidin 3-O-glucoside, and isoliquiritigenin showed higher inhibitory activities in a concentration-dependent manner. Structure-activity relationship analysis revealed that introducing hydroxyl groups to C3', C4', and C6 of the flavonoid structure was beneficial to improving the inhibitory efficacy against DPP-4, whereas the hydroxylation at position 3 of ring C in the flavonoid structure was unfavorable for the inhibition. Besides, the methylation of the hydroxyl groups at C3', C4', and C7 of the flavonoid structure tended to lower the inhibitory activity against DPP-4, and the 2,3-double bond and 4-carbonyl group on ring C of the flavonoid structure was essential for the inhibition. Glycosylation affected the inhibitory activity diversely, depending on the structure of flavonoid aglycone, type of glycoside, as well as the position of substitution. Inhibition kinetic analysis suggested that myricetin reversibly inhibited DPP-4 in a non-competitive mode, wheareas hyperoside, narcissoside, cyanidin 3-O-glucoside, and isoliquiritigenin all reversibly inhibited DPP-4 in a mixed type. Moreover, the fluorescence quenching analysis indicated that all the five flavonoid compounds could effectively quench the intrinsic fluorescence of DPP-4 by spontaneously binding with it to form an unstable complex. Hydrogen bonds and van der Waals were the predominant forces to maintain the complex of myricetin with DPP-4, and electrostatic forces might play an important role in stabilizing the complexes of the remaining four flavonoids with DPP-4. The binding of the tested flavonoids to DPP-4 could also induce the conformation change of DPP-4 and thus led to inhibition on the enzyme. Molecular docking simulation further ascertained the binding interactions between DPP-4 and the selected five flavonoids, among which hyperoside, narcissoside, cyaniding 3-O-glucoside, and isoliquiritigenin inserted into the active site cavity of DPP-4 and interacted with the key amino acid residues of the active site, whereas the binding site of myricetin was located in a minor cavity close to the active pockets of DPP-4.